The Images of a Minister Built through the Use of Ecclesiastical Words in Emersonâ€™s â€œThe Problemâ€ - Trihastuti, Chatarina; Putranti, Adventina (Universitas Sanata Dharma, 2014)
â€œThe Problemâ€, a poem by Ralph Waldo Emerson, expresses Emersonâ€™s preoccupation with the problem of vocation. It is about Emersonâ€™s dilemma of his admiration toward church leaders despite his refusal to remain within their ranks. â€œThe Problemâ€ is analyzed from its diction -which consists of ecclesiastical words- to create images that can help the readers understand the poem. This study covers two main problems. The first is dedicated to find the meaning of the ecclesiastical words- especially those that are related to a minister- in â€œThe Problemâ€ and the second is devoted to find the images created from the ecclesiastical meanings in the previous problem.The results of this analysis show that in â€œThe Problemâ€ there are twelve expressions containing ecclesiastical meanings. The ecclesiastical meaning of a word is sometimes different from the general meaning. The ecclesiastical meaning is more specific than the general meaning. The second finding is that the ecclesiastical meanings can result in the perception of six images. The first is about the poetâ€™s liking of the job of a minister and its burdens as well. The second shows that the poet would be a minister, with all of its burdens, even though he cannot see a ministerâ€™s faith yet. The third is about the poetâ€™s hesitance to be a minister. The fourth is that the Church with its host, chanting choir, and priest Christianize the people. The fifth is about the Bible and the prophets that teach about God and salvation. The sixth is about the poetâ€™s admiration toward Chrysostom, Augustine, and Taylor and also the reason why he chose to leave the ministry.Keywords: ecclesiastical words, images